Hybrid Passive Cooling System for Rooftop Photovoltaics with Varying Height Clearances - Fauzi, Pebi Dian; Kusumanto, RD.; Hasan, Abu (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
The increasing adoption of rooftop photovoltaic (PV) systems as a renewable energy source is often hindered by the negative impact of high operating temperatures on their efficiency. To address this, a hybrid passive cooling system offers a promising solution to enhance the power output of PV panels while supporting environmental sustainability. This study investigates the effects of varying the height clearance between a PV panel and the roof surface on the thermal performance and energy efficiency of a hybrid passive cooling system. The research integrates a passive cooling setup, which utilizes natural airflow without additional energy consumption, with a thermoelectric generator (TEG) based on a Peltier module to convert waste heat into supplementary electrical energy. The study employed both simulation and experimental methods to analyze the thermal and energy performance of the system at different height configurations. Five identical 30W Maysun solar panels were tested at heights of 1 cm, 5 cm, 10 cm, 15 cm, and 20 cm, with data on temperature and voltage collected throughout the day. The results indicate that increasing the installation height significantly improves air circulation, leading to lower panel temperatures and higher voltage outputs. The optimal configuration was found to be at a height of 20 cm, which consistently yielded the highest voltage. Furthermore, the integration of a Peltier module with a heatsink proved effective, generating up to 623 mV of additional voltage by converting waste heat. These findings provide valuable insights and practical recommendations for designing more efficient rooftop PV installations, contributing to the advancement of sustainable building technologies and the global effort to reduce carbon emissions.